2018
DOI: 10.3390/rs10040628
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Approach for Fog Retrieval Based on a Combination of Satellite and Ground Truth Data

Abstract: Fog has a substantial influence on various ecosystems and it impacts economy, traffic systems and human life in many ways. In order to be able to deal with the large number of influence factors, a spatially explicit high-resoluted data set of fog frequency distribution is needed. In this study, a hybrid approach for fog retrieval based on Meteosat Second Generation (MSG) data and ground truth data is presented. The method is based on a random forest (RF) machine learning model that is trained with cloud base a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…As previous studies (e.g., Cermak and Knutti, 2009;Lee et al, 2011;Egli et al, 2016;Nilo et al, 2018) have shown, geostationary satellites have the potential to draw a spatiotemporally coherent picture of the occurrence of fog and low clouds (FLCs). However, information on FLCs from satellites is typically inferred using separate daytime (e.g., Bendix et al, 2006;Cermak andBendix, 2008, 2011;Nilo et al, 2018) and night-time (e.g., Ellrod, 1995;Cermak and Bendix, 2007) algorithms, disrupting our view of fog development at a critical time of its life cycle, as typically, shortwave radiative heating starts the dissipation of fog shortly after sunrise (Tardif and Rasmussen, 2007;Haeffelin et al, 2010;Waersted et al, 2017). This break in retrieval techniques has thus limited the applicability of satellite-based FLC observations for the analysis of entire fog life cycles.…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies (e.g., Cermak and Knutti, 2009;Lee et al, 2011;Egli et al, 2016;Nilo et al, 2018) have shown, geostationary satellites have the potential to draw a spatiotemporally coherent picture of the occurrence of fog and low clouds (FLCs). However, information on FLCs from satellites is typically inferred using separate daytime (e.g., Bendix et al, 2006;Cermak andBendix, 2008, 2011;Nilo et al, 2018) and night-time (e.g., Ellrod, 1995;Cermak and Bendix, 2007) algorithms, disrupting our view of fog development at a critical time of its life cycle, as typically, shortwave radiative heating starts the dissipation of fog shortly after sunrise (Tardif and Rasmussen, 2007;Haeffelin et al, 2010;Waersted et al, 2017). This break in retrieval techniques has thus limited the applicability of satellite-based FLC observations for the analysis of entire fog life cycles.…”
Section: Introductionmentioning
confidence: 99%
“…It employs the station altitude and subtracts the mean altitude of surrounding pixels in its vicinity. Positive values indicate a summit position, whereas negative values indicate a valley position (Egli et al, 2018). Again, a window size of 20 km was chosen.…”
Section: Eea Demmentioning
confidence: 99%
“…Machine learning methods such as random forests [23] are increasingly being applied to remote sensing tasks including cloud classification. Similar to the threshold based approaches, methods such as support vector machines (SVM) [24] and random forests (RF) [8] focus on classification of individual pixels. They are available as ready-to-use methods [25] and are also used to derive cloud-related products such as rainfall retrievals [26].…”
Section: Related Workmentioning
confidence: 99%
“…Methods relying only on spatial properties are developed [29] or adapted from other domains [30]. Spatial information in the form of handcrafted texture features are also used for machine learning approaches such as RF [8]. However, identifying and handcrafting relevant spatial features is a cumbersome and time-consuming task.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation